Entamoeba histolytica Incidence in District Dir Lower and Tehsil Wari Upper Dir Khyber Pakhtunkhwa, Pakistan - Nisar , Muhamamd; Khan , Fawad; Ahmad, Nisar; Saeed Ullah; Inayat Ul Haq; Ahmad, Sayad; Asad Ullah; Muhammad Saad; Jalwa; Nasir, Fawad (Indus Journal of Bioscience Research, 2024)
Entamoeba histolytica, a protozoan parasite responsible for amebiasis, remains a significant public health challenge in Pakistan, particularly in regions like the Lower and Upper Dir districts of Khyber Pakhtunkhwa. This study provides an epidemiological analysis of the prevalence, seasonal distribution, and demographic patterns of E. histolytica infections across seven tehsils—Timergara, Balambat, Khall, Warae, Maidan, Samar Bagh, and Jandool—covering a total of 3927 cases in 2020. The findings show notable variations in disease prevalence, with Balambat (1000 cases) and Timergara (800 cases) being the most affected tehsils. A peak in infections was consistently observed during the summer months of May and August, likely due to increased water contamination during the monsoon season. The age-specific analysis indicated that children aged 6-15 years were the most affected group, comprising 41.3% of total cases, while males (66%) were more affected than females (34%). Warae Tehsil, part of Upper Dir, reported 450 cases, with a higher burden in rural villages such as Toor Mung Kalone and Jugha Banj, where access to healthcare is limited. The study emphasizes the need for region-specific interventions, including improvements in water quality, enhanced health education, and strengthened disease surveillance systems to curb the spread of E. histolytica. These strategies are essential for reducing the public health burden and preventing future outbreaks in the region. This research not only provides critical insights into the epidemiology of E. histolytica in high-risk areas but also establishes a foundation for targeted public health interventions, ultimately contributing to a more comprehensive understanding of parasitic diseases in Pakistan’s rural landscapes